PENERAPAN INSTRUMEN KUESIONER PRA-SKRINING PERKEMBANGAN DALAM PENGEMBANGAN SISTEM INFORMASI SKRINING BAHASA ANAK - Admadja, Elang; Muflihah, Yusrida; Arifiana, Isrida Yul (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
This research focuses on creating a website-based child language development screening system that helps clients find language development disorders in children earlier. The purpose of the research is to design a website-based child language development screening system, implementing the Developmental Pre-Screening Questionnaire on the website. The research method used is the waterfall method, because the steps of this method are sequential, from the requirement stage to maintenance. In the development of this system, the Developmental Pre-Screening Questionnaire is applied as the main tool to identify potential language delays in children. System testing is carried out using the Black box and UMUX-Lite methods to ensure that the system functions in accordance with the specifications made and effectively meets user needs. Black box testing results show that the system runs according to the requirements made, while UMUX-Lite results get a score of 81.4 from 15 respondents who have children aged 1-5 years, indicating that the system gets an acceptability score in Acceptable. Based on the results obtained, it is concluded that the Child Language Word system is successful and meets the client's needs, and becomes a useful tool for detecting early childhood language development disorders.